Hubungan Antara Pengaruh Kepemimpinan Terhadap Kinerja Karyawan pada Perusahaan Otomotif - Salsabilah, Salwa Zahirah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to investigate the influence of leadership on employee performance in the automotive industry. Good leadership plays a crucial role in motivating employees, increasing productivity, and creating job satisfaction, which ultimately affects the overall performance of the organization. Through a literature review approach, this study analyzes relevant theories and examines empirical findings from previous research discussing the relationship between leadership style and employee performance levels within the automotive industry. The research findings indicate that leaders who are able to inspire, maintain trust, and demonstrate high integrity will create a work environment that supports optimal performance. Conversely, poor leadership can reduce work motivation and decrease productivity and the quality of work outcomes. Therefore, automotive companies need to ensure that individuals in leadership positions have the capability to provide explicit guidance, build constructive interpersonal relationships with employees, and encourage innovation within the organization.